Delay or travel time information? The impact of advanced traveler information systems on drivers' behavior before freeway work zones. (May 2022) - Reinolsmann, Nora; Alhajyaseen, Wael; Brijs, Tom; Pirdavani, Ali; Ross, Veerle; Hussain, Qinaat; Brijs, Kris
Highlights: Variable message signs benefit from delay updates for strategic freeway diversions. Graphical displays increase rerouting by additional 25% for time-wise equal routes. VMS displaying total travel times are less effective than traffic delay displays. Repetition of traveler information is beneficial if both freeway routes have delays. Highlighting the contrast in traffic delays motivates drivers to take a detour. Abstract: Peak travel times contribute to congestion formation at freeway work zones. Advanced Traveler Information Systems (ATIS) can inform drivers in real-time about the delays and travel times en-route and can provide information about an alternative route to a destination. Different ATIS display strategies are available; however, road authorities lack insights into how time display methods and sign characteristics influence the driving behavior (decelerations, lateral position), the drivers' attention allocation ability and the subsequent route choice before the freeway diversion. A driving simulator study was conducted with 80 drivers in the State of Qatar to investigate drivers' behavior and voluntary route choices when encountering total travel time (default setting) or delay time updates for two freeway routes on Variable Message Signs (VMS) and Graphical Route Information Panels (GRIP). The GRIPs are a graphical alternative to conventional VMS that can provide drivers with a visual map of the most direct route or an alternative less congested route to a destination using different color schemes. The time difference ratio between the two routes was kept constant to compare the effectiveness of the information designs and investigate the drivers' attention towards the signs with an eye-tracker. The results showed that the display of zero delays for a detour did influence 74–83% of the drivers to take the alternative route when being displayed on a VMS and a GRIP with free flow attribute framing. When displaying equal total travel times, the GRIP did influence 25% more drivers to follow the alternative route than the VMS. Generally, displaying zero delays for the alternative route resulted in an efficient attention allocation to the first ATIS location and fewer mean decelerations before the repeated ATIS location nearing the diversion. Road authorities are advised to activate the display of delay times to support efficient route choices among freeway drivers.